Post Appendectomy Complication Analysis at Karnali Academy of Health Sciences Teaching Hospital, Jumla - Thapaliya, Narad Prasad; Menyengbo, Suryaman; Rain, Abdullah; Thapa , Nabin; Bista, Binamra (Journal of National Heart and Lung Society Nepal, 2024)
Background: Acute Appendicitis is common surgical disease throughout the world and Appendectomy is common surgical Emergency operation.The Aims of this study is to analyse post appendectomy complications at Karnali Teaching Hospital, Jumla, Nepal. Methods: This is Retrospective study conducted at the Karnali Teaching Hospital over a periods of Two years (2021-2023) under the Department of Surgery,Karnali Academy of Health Sciences,Jumla-which is Rural community based Hospital.The Datas were analysed by appropriate statistical tools. Results: A Total of 70 Appendectomy performed over that periods and amongs them 36(51.5%) were Females and 34 (48.5%) were males. Main post surgical complications were postoperative Ileus (7%), SSI (4.3%) and seroma (2.8%). Anaesthesia related complications were found more significant in our study,in compare to other studies. Conclusion: Post Appendectomy surgical complications were relatively low in our study,its may be due to high altitude but post- anesthetic complications were relatively high.